(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to conduct a content analysis of library resources in librariesthrough their respective library websites. Library resources include materials such as books, journals,audiovisual materials, and online databases, among others. The study aims to analyze the types andamount of resources available on library websites, the ease of access to these resources, and the qualityof information provided on the websites. The study will use a mixed-methods approach, combining bothqualitative and quantitative data analysis methods. The sample for the study will consist of a selection oflibraries from different countries and regions, including academic, public, and special libraries. Theselection of libraries will be based on their availability online and their reputation as a reliable source ofinformation.